Tratamiento contable de los costos de concesión y exploración en la empresa minera Oro & Metales El Inca S.A. - Solorzano Gutierrez, Karen Anahela; Fares Uyaguari, Jahir Alejandro (Machala : Universidad Técnica de Machala, 2024)
The mining activity plays a crucial role in the economy of any country, this research work focuses on the analysis and identification of the accounting treatment given to the mining concession and those costs incurred in the exploration phase, guided by the provisions of the IFRS for SMEs, specifically Section 34, which tells us about how to record and measure accounting costs incurred during the exploration and evaluation of resources, the standard establishes key points to take into consideration for the international understanding of the information presented, focusing only on the exploration of the deposit, it was observed that the lack of understanding of the same has generated some difficulty in accounting for such costs and therefore, affected the understanding of the same. The methodology used for this study focused on obtaining key information directly from the person in charge of the accounting area through the application of an open interview. The variability in the interpretation of the IFRS has generated some discrepancy at the time of recording costs, so it has been suggested to the company to carry out constant training to the personnel in charge of the accounting department in order to keep them updated and allow them to perform their activities efficiently.
La actividad minera juega un papel crucial en la economía de cualquier país, este trabajo de investigación se centra en el análisis e identificación del tratamiento contable brindado a la concesión minera y aquellos costos incurridos en la fase de exploración, guiándonos de lo establecido en la NIIF para Pymes, específicamente la Sección 34, quien nos habla sobre como registrar y medir contablemente los costos emitidos durante la exploración y evaluación de recursos, la norma establece puntos clave a tomar a consideración para el entendimiento internacional de la información presentada, centrándonos únicamente en la exploración del yacimiento, se pudo observar que la falta de entendimiento de la misma ha generado cierta dificultad para contabilizar dichos costos y por ende, afectado la comprensión de la misma. La metodología utilizada para este estudio se centró en la obtención de información clave por parte directa del encargado del área contable a través de la aplicación de una entrevista abierta. La variabilidad en la interpretación de la NIIF ha generado cierta discrepancia al momento de registrar los costos, por lo que se ha sugerido a la empresa, realizar capacitaciones constantes al personal de trabajo encargada del departamento contable con el fin de mantenerlos actualizados y permitan realizar sus actividades de manera eficiente.
Keywords: NIIF; CONTABILIDAD DE COSTOS; CONCESIÓN; EXPLORACIÓN